Pharmacologic Prophylaxis of Portal Venous System Thrombosis after Splenectomy: A Meta-Analysis - Xingshun Qi; Ming Bai; Xiaozhong Guo; Daiming Fan (Gastroenterology Research and Practice)
Portal venous system thrombosis (PVST) is a life-threatening complication of splenectomy. A meta-analysis was conducted to explore the role of pharmacologic prophylaxis of PVST after splenectomy. Overall, 359 papers were initially identified via the PubMed, EMBASE, and Cochrane Library databases. Eight of them were eligible. The incidence of PVST after splenectomy was significantly lower in patients who received the preventive measures than in those who did not (odds ratio [OR]: 0.33, 95% confidence interval [CI]: 0.22–0.47, P<0.00001). Subgroup analyses demonstrated that the significant difference remained in studies including patients with portal hypertension (n=6), but not in those including patients with hematological diseases (n=2); the significant difference remained in studies using any type of prophylactic drugs (anticoagulants [n=6], thrombolytics [n=1], and prostaglandin E1 [n=1]); the significant difference remained in nonrandomized studies (n=5), but not in randomized studies (n=3). The risk of bleeding was similar between the two groups (OR: 0.65, 95% CI: 0.10–4.04, P=0.64). In conclusion, pharmacologic prophylaxis might decrease the incidence of PVST after splenectomy in patients with portal hypertension and did not increase the risk of bleeding. However, the effect of pharmacologic prophylaxis of PVST in patients with hematological diseases remained questioned.